Clinical audit /QIP report: rhythm checks for patients admitted to the Hyper Acute Stroke Unit (HASU) - Binisha Joshi; Paul Bolaji; Taba Ismael (Future Healthcare Journal)
Introduction: Atrial fibrillation (AF) and other cardiac arrhythmias significantly increase the risk of ischaemic stroke. Early detection and appropriate management of rhythm abnormalities in the Hyper Acute Stroke Unit (HASU) are essential for preventing recurrent strokes and improving patient outcomes. This audit evaluated compliance with rhythm-monitoring protocols in HASU, focusing on the use of continuous telemetry and documentation practices. Methods: This quality improvement project (QIP) involved a retrospective review of all HASU patient records over 1 month from December 2024 to January 2025. Patient records, discharge summaries and rhythm-monitoring reports were analysed to assess the frequency of monitoring, documentation of findings and subsequent clinical actions. A standardised data collection sheet was developed to capture key metrics, including in-hospital rhythm monitoring, its effectiveness in detecting arrhythmias and the need for outpatient Holter monitoring. Results: The QIP evaluated different aspects, included rhythm monitoring compliance, arrhythmia detection and documentation practices in HASU. 100% of patients admitted to HASU underwent 72-h telemetry monitoring. 32.7% of patients had AF; 18.1% had a pre-existing AF. 14.5% had newly diagnosed AF identified through cardiac monitoring; among them, 75% were detected after more than 24 hours of monitoring. None of the patients diagnosed with AF during admission required outpatient telemetry, reducing both financial burden and waiting times. However, despite high compliance with telemetry use, deficiencies were noted in the documentation of rhythm monitoring outcomes, with only 25% having complete documentation, while 7.2% had no ECG documentation in standard records. This highlights the need for a standardised recording system. Conclusion: Early telemetry is a valuable tool for detecting paroxysmal AF, aligning with national guidelines that report AF detection rates of 2–4% with standard ECG and 2.4–18.5% with telemetry.1,2 To enhance clinical documentation and ensure seamless integration into patient care, we propose the implementation of a standardised telemetry documentation system. This includes a dedicated telemetry section in electronic patient records, a structured template within patient care flows and the use of preformatted documentation stickers for bedside notes. These interventions will improve clarity, auditability and continuity of care, ultimately optimising patient safety, resource utilisation and stroke prevention strategies in HASU.